Environmental analysis of organic waste treatment focusing on composting scenarios - Oliveira, Luiza S.B.L. (2017)
The correct disposal of the waste generated by human activities is one of the prevalent challenges that the world faces towards a sustainable development. The lack of suitable sites and the high cost of waste treatment have persuaded many municipalities to implement a policy for integrated waste management, which includes measures such as, source reduction, reuse, recycling, composting and final disposal in landfill. This study examined the alternatives for composting of the organic waste generated in the city of Bauru, in the state of São Paulo, which does not have a composting plant, and analyzed the environmental impacts of seven scenarios: current situation, in which all organic waste is disposed at the landfill; dispatch of the organic waste generated in the city to the closest municipality having a composting plant; construction of a composting plant in Bauru; use of home composting for 10%, 25%, 60% and 90% of organic waste. The method consisted of literature review, data collection among the company responsible for the waste management in the municipality, and the Life Cycle Assessment of the scenarios through the software IWM-2 for the Life Cycle Inventory and Recipe2008 conversion factors for the following impact categories: climate change, ozone depletion, particulate matter formation, and human and freshwater toxicity. The results showed that home composting must be followed by a reduction in the organic waste collection days, in order to have a positive effect in the greenhouse emissions derived from transportation and collection. Also home composting has a greater potential to reduce carbon dioxide equivalent emissions per mass of waste composted in comparison with composting plants. The use of transfer station can have a positive effect on composting plants that are located in other municipalities.